Role of the Modified WHO Partograph in Improving Maternal and Neonatal Outcomes: A Prospective Observational Study - Sukeshini Bhagat; Shreyasi Chiwadshetti; Chhavi Kowe; Renema Datta; Mahesh Shinde; Pushti Shah; Divya Yadav; Samreen Chunawala; Abhay Gupta; Natanshi Kumar; Pranav Ghuge; Prajakta Kokane (BioMed Target Journal, 2025)
Childbirth requires close monitoring to ensure maternal and infant safety. Effective labor monitoring helps detect complications early, reducing risks. In 2017, WHO reported 295,000 maternal deaths, mostly in low- to middle-income countries, highlighting the need for improved care. The WHO partograph, a graphical labor-monitoring tool, aids in tracking progression and guiding timely interventions. Therefore, the present study aimed to evaluate the role of the modified WHO partograph in reducing maternal and neonatal morbidity, minimizing prolonged labor, and guiding delivery decisions. This prospective observational study at a tertiary care center included 155 patients over one year, following ethics approval. It included the term, singleton pregnancies in cephalic presentation and excluded high-risk cases. Informed consent was obtained, and examinations were conducted, including a nonstress test (NST).  Labor was monitored using the modified WHO partograph, assessing fetal heart rate, uterine contractions, and maternal vitals. Labor management followed standard protocols. This study included 155 patients: 125 had full-term normal delivery, 15 had instrumental delivery, and 15 underwent lower-segment cesarean section (LSCS).  Labor induction (33 patients) significantly impacted delivery mode and maternal-fetal outcomes. Maternal and fetal morbidity increased beyond the alert line, with higher postpartum hemorrhages (4%), sepsis (4%), and neonatal complications. APGAR scores decreased after the action line but improved at five minutes, which highlights the importance of timely intervention. Findings were statistically significant (p < 0.0001) for differences in morbidity rates and APGAR scores. The study highlights the partograph's essential role in labor monitoring and recommends its routine use to improve management, prevent complications, and ensure maternal and neonatal safety. Hence, it is very important to use a partograph in labor.